RANCANG BANGUN ROBOT PEMINDAH BARANG BERBASIS MIKROKONTROLER - Budi Pramono; Irene ongkowijoyo (UNIVERSITAS STEKOM, 2020)
This study generally aims to design an information system that can handle problems in putting and sorting goods into warehouses at CV. Sekar Intan KIC Gatsu, Semarang. In terms of using the Information System, CV. Sekar Inran KIC Gatsu, Semarang. In the transfer and sort of goods in the warehouse still using a manual. system when the implementation, warehouse employees must take and place the goods to the warehouse that has been determined each - each type of item, so employees must calculate the number of items when the goods take place.